2019
DOI: 10.3846/jcem.2019.9621
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Evolutionary Governance in Mega Construction Projects: A Moderated Mediation Model of Relational Contract and Transaction Cost

Abstract: Mega construction project governance is an evolutionary process characterized by high transaction costs and complex interrelationships. Based on transaction cost theory, relational contract theory and evolutionary governance theory, this study explored the impact of evolutionary project governance on mega construction project performance by collectively considering the mediating effect of transaction costs and the moderating effect of a relational contract. Partial least squares structural equation modeling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…However, monetary incentives increase the government budget and total cost. Furthermore, blind increases in the amount of a bonus or a penalty is not an effective method to guide an investor's behavior (Girth, 2017; Wang et al , 2019). Hence, incentives derived from psychological mechanisms, such as trust and intrinsic motivation, gradually attract research attention.…”
Section: Uncertainty and Contractual Flexibilitymentioning
confidence: 99%
“…However, monetary incentives increase the government budget and total cost. Furthermore, blind increases in the amount of a bonus or a penalty is not an effective method to guide an investor's behavior (Girth, 2017; Wang et al , 2019). Hence, incentives derived from psychological mechanisms, such as trust and intrinsic motivation, gradually attract research attention.…”
Section: Uncertainty and Contractual Flexibilitymentioning
confidence: 99%
“…RC papers were analysed for both objective and subjective definitions to provide more relevant and valuable social research, as subjective accounts suffer from a lack of clarity. Objectivity and subjectivity in RC definitions were found primarily by identifying subjective elements, or linguistic expressions; in other words, lexical phrases (Wiebe et al 2004) Although the subjective elements were identified, they were not used because they were categorised as flexible or soft elements which are often hard-tomeasure, synonyms of the same terms, which are open to interpretation (Strahorn et al 2017, Wang et al 2019. However, clustering of sentences containing subjective elements (based on similarity) helped to trace back the terminology to Macneil's literary works.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…trust), meaning each individual has different experiences of trust (Strahorn et al 2017). For example, "trust", fundamentally hard-to-measure, can mean, without a benchmark, any varying degree of achievement in confidence (Strahorn et al 2017, Wang et al 2019).…”
Section: Analysis Ii: Definitions Of Relational Contractingmentioning
confidence: 99%
“…In low-risk situations, contractual governance at a higher level is more effective in improving performance [23]. e most active citing article offered a model to test the effect of transaction cost and relational governance [52]. In project, control and trust are "the endpoints of a continuum" [68] as complements of each other rather than substitutes [70].…”
Section: Analysis Of Cocitation Clustersmentioning
confidence: 99%